2011
DOI: 10.1164/rccm.201106-0975oc
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Respiratory Events with and without Cortical Arousal in Obstructive Sleep Apnea

Abstract: Rationale: A total of 20-30% of respiratory events in obstructive sleep apnea are terminated without clear arousal. Arousals are thought to predispose to further events by promoting hyperventilation, hypocapnia, and upper-airway dilator muscle hypotonia. Therefore, events terminated without arousal may promote stable breathing. Objectives: To compare physiologic changes at respiratory event termination with American Sleep Disorders Association (ASDA) Arousal to No Arousal, and determine whether secondary respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 30 publications
2
63
1
Order By: Relevance
“…The pattern of changes in minute ventilation and dilator muscle activity following arousal, for both arousal intensity categories, are similar to those previously presented by Jordan and colleagues 9 for ASDA (American Sleep Disorders Association) scored arousals. Increases in ventilation and dilator muscle activity following cortical arousal, according to standard definitions of arousal, have also been reported in other studies.…”
Section: Effects Of Arousal Intensity On Ventilatory and Upper Airwaysupporting
confidence: 87%
See 1 more Smart Citation
“…The pattern of changes in minute ventilation and dilator muscle activity following arousal, for both arousal intensity categories, are similar to those previously presented by Jordan and colleagues 9 for ASDA (American Sleep Disorders Association) scored arousals. Increases in ventilation and dilator muscle activity following cortical arousal, according to standard definitions of arousal, have also been reported in other studies.…”
Section: Effects Of Arousal Intensity On Ventilatory and Upper Airwaysupporting
confidence: 87%
“…2 An unnecessarily large increase in ventilation following arousal can contribute to subsequent hypocapnia, destabilization of the ventilatory control system, and the cyclical breathing pattern that occurs in OSA. 2,8,9 More recently, Azabarzin and colleagues used an…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the majority of MAS activations occurred more frequently after respiratory events with arousal response than those without, as previous studies have also reported for the MAS and other craniofacial muscles. [2][3][4]23 Although previous studies have shown that cardiac arousals without visually detectable EEG changes have been detected after respiratory events, 18,21,23,28 these respiratory events were found to be rarely associated with MAS contractions. This is consistent with the findings of the recent studies in which respiratory efforts and electromyography of the tongue muscles were assessed in relation to respiratory events.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of the recent studies in which respiratory efforts and electromyography of the tongue muscles were assessed in relation to respiratory events. 23,29,30 However, when transient arousals with visually identifiable EEG changes (e.g., mAR, AW) occurred after respiratory events, the MAS was activated. This result supports a previous suggestion of an association between MAS and arousal response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation